(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
The University of Valladolid was closed on February 8, 1975, by the Council of Ministers, presided over by the then Head of State, General Francisco Franco Bahamonde. Academic activities (theoretical and practical classes and the regular June exams) were suppressed. The University of Valladolid was only reopened in September 1975 to allow for the extraordinary exams; there was practically a general pass rate, which further worsened the situation. This closure produced severe demoralization among students and faculty that persisted for a long time, seriously deteriorating the situation. At the beginning of the 1970s, the faculty was grouped into three sociological groups: the pseudo-left, the progressive center group (the predominant tendency), and the traditional right. The pseudo-left professors were made up of young professors from peripheral universities (Andalusia, Valencia) who had obtained professorships through a competitive examination among professors. Associate professors who were not fully integrated into the city and the University. Between 1975 and 1983, the Dean’s Office and management positions were held by professors belonging to the progressive center group. In 1978, the New University Clinical Hospital was opened, and its staff included professors of clinical subjects and some professors of basic medical sciences (Biochemistry, Physiology, Pharmacology, Histology, etc.). The curriculum in force at the Faculty of Medicine of the University of Valladolid was the 1973 plan, which lasted from 1973 to 1992, when it was replaced by a plan adapted to the spirit of Bologna (the European Common Area). The Spanish University was governed from 1970 to 1983 by the General Education Law, and from 1983 onward by the University Reform Law, adapted to the spirit of the Bologna Agreement. From 2010 onwards, the Bologna spirit. Doctoral studies from 1975 to 1985 were governed by the provisions issued by the Ministry of Education under Ruiz Jiménez in 1954. From 1985 onwards, they were governed by new provisions issued by Minister Maravall, modified in 1998 by Mariano Rajoy. In 2010, Minister Ángel Gabilondo adopted doctoral studies in the Bologna spirit and regulated their evaluation by ANECA (an evaluation agency dependent on the Ministry of Universities and Research that accredited research activity (six-year research period) and the quality of the teaching staff, who required a prior ANECA report to apply for teaching positions in Spanish universities). The teaching activity of all medical schools was modified by the implementation in Spain, starting in 1978, of the MIR (Medical Interns and Residents) System, controlled by the Ministry of The Health Department’s approach to accessing specialized medical training and the scores obtained by applicants to the MIR system were once used to evaluate medical schools in our country. Today, this system is no longer valid due to the existence of academies that prepare for the MIR system, which standardize student scores, eliminating the differences in training across medical schools.